Integrating STATCOM and Battery Energy Storage System for Power System Transient Stability: A Review and Application. (17th December 2012) - Chakraborty, Arindam; Musunuri, Shravana K.; Srivastava, Anurag K.; Kondabathini, Anil K.
Abstract : Integration of STATCOM with energy storage devices plays an imperative role in improving the power system operation and control. Significant research has been done in this area for practical realization of benefits of the integration. This paper, however, pays particular importance to the performance improvement for the transients as is achievable by STATCOM with battery-powered storage systems. Application of STATCOM with storage in regard to intermittent renewable energy sources such as wind power generation is also discussed in the paper. At the beginning of this paper, an overall review of the STATCOM and energy storage systems are elaborated. A brief overview of the advantages of using STATCOM in conjunction to energy storage systems in achieving power system stability is presented. In the second part of the paper, a typical transient stability model of a STATCOM is presented. The dynamics of real and reactive power responses of the integrated system to transients is studied. The study is aimed at showing that the combination of STATCOM and battery energy storage significantly improves the performance of the system. The final results show that the STATCOM reactive power/voltage control helps in transient stability enhancement.